(untitled) (Global Journal of Management and Business Research, 2023)
This survey paper traverses the field of website-based solutions from the outlook of enhancing the work efficiency of any organization or institution particularly establishment with less technically skilled workforce The paper provides a comprehensive overview on web development in a great way spanning from the state of the field current trends important technologies and evaluating data across the sub domains of the paramount technological footprints Discussion on hurdles faced by developers in creating solutions using optimal tech pool We have provided context and motivation for future developers by compiling summaries for various research work that has been documented in formal of articles journals conference papers etc Both the aspects of frontend and backend are being taken into consideration as well as their integration for the build out of a working real-world project We have also discussed the key bottleneck areas that may become hinderance for the beginners in this field while also assisting the experts on points further research and exploration